MR diffusion is sensitive to mechanical loading in human intervertebral disks ex vivo. Issue 3 (3rd June 2014) - Alkalay, Ron N.; Burstein, Deborah; Westin, Carl‐Fredrik; Meier, Dominick; Hackney, David B.
<x xml:space="preserve">Abstract</x> Purpose To use T2 and diffusion MR to determine the change in the mechanical function of human disks with increased degenerative state. Materials and Methods Spatial changes in T2 and diffusion were quantified in five cadaveric human lumbar disks under compressive loads. Regression models were used to investigate the relationship between the change in MR parameters and the disk's dynamic and viscoelastic properties. Results Compressive loading caused a significant reduction in the disk's mean diffusivity ([11.3 versus 9.7].10−4.mm2/s, P < 0.001) but little change in T2 (P < 0.05). Diffusivity and T2 were correlated with the disk's dynamic (P < 0.01 and P < 0.05) and long‐term viscoelastic (P < 0.05 and P < 0.05) stiffness. Diffusivity but not T2, was correlated with its viscoelastic dampening (r2 = 0.45, P < 0.01) and instantaneous stiffness (r2 = 0.44, P < 0.05). Nucleus diffusivity was significantly higher than the annulus's (−21% to −4%, P < 0.01). MR‐estimated hydration was correlated with the instantaneous viscoelastic stiffness of the nucleus (r2 = 0.35, P < 0.05) and the dynamic (r2 = 0.44, P < 0.05) and long‐term viscoelastic (r2 = 0.42, P < 0.05) stiffness in the annulus. T2 correlated with diffusivity at low load (r2 = 0.66, P < 0.05), but not at high load. Conclusion The strong correlations between diffusivity and the rheological assessments of disk mechanics suggest that MR might permit quantitative assessment of disk functional status and structural integrity. J. Magn. Reson. Imaging 2015;41:654–664. © 2014 Wiley Periodicals, Inc.